The prevention of obesity starting from the kindergarten by means of peer educator mothers and WhatsApp messages - Vairano, M. P.; Russo Krauss, P.; D'Agnese, P.; Iavarone, F.; Rice, R.; Strangio, F.; Pezone, G. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Early-life diet plays a crucial role in the development of body weight issues. We therefore investigated the effectiveness of a peer-education intervention, aiming at encouraging the intake of fruits and vegetables and of a healthy mid-morning snack, targeting the mothers of 3-8 years old children attending kindergarten and primary school. Study design. Experimental approach. Methods. The study involved 924 children (intervention group) and 450 children (control group). The intervention was carried out by organizing three meetings at school with the participation of healthcare professionals, mothers and teachers in a maieutic way. The meetings focused on i) discussing the issues that mothers face with their children’s nutrition; ii) possible solutions; iii) identification of “leading mothers” playing as peer-educators. As control a similar intervention targeting only the teachers, without involving the mothers, was also carried out. The effectiveness of such interventions was evaluated by external evaluators, before, the interventions and 3 and 9 months after the interventions. Results. The check, carried out 3 months after the intervention, showed a significant improvement with respect to the mid-morning snack, and the consumption of the main dishes as well as fruits; the check carried out 9 months after the intervention, showed that such improvements were maintained in the case of the midmorning snack and the fruit intake. No improvement was observed in relation to the control group. Conclusions. This is the first example of an intervention promoting a healthy diet involving mothers of children attending kindergarten and primary school as peer educators and it actually improved the dietary habits.